Learning environment for operational amplifiers in IC - Robina, Akter Mim (2019)
Research has shown learning online have been significantly beneficial to students as compared to traditional classroom learning [1]. It allows students to be independent learners and also keep them learning on the go as the materials are updated constantly. With the ease of flexible schedule and learning environment, students are able to learn materials better and command greater self-satisfaction from completing tasks independently. Hence, online learning is growing in popularity as the preferred method for education. However, students are required to possess self-motivation and determination to complete the tasks and this causes some students to be unable to keep up with the pace [2]. With the lack of a physical teacher, their queries are not answered promptly, and they may fall behind in understanding the content throughly. Therefore, it is important for online learning platforms to be engaging and interactive with access to online teachers to cater to all students. A discussion forum will ensure a strong support system and also as a platform to generate interaction between students. The objective of this project is to create interactive e-learning platform for Operational Amplifiers. The author has developed an interactive e-learning environment using Moodle as well as HTML, CSS and JavaScript coding that is able to meet the objective of the project. This project contains various user interaction features such as quizzes and lectures.